Understanding what violent street crime, globalization, and ice cream have in common - LaFree, Gary (Criminology & public policy, 2025)
Research Summary In recent years, nutrition researchers have found that ice cream may have as many health benefits as low-fat milk or yoghurt for those with diabetes or at risk of diabetes. Nonetheless, they have resisted reporting this finding to the media, the public, or other researchers. This observation got me thinking about how preconceived assumptions and biases affect social science in general and criminology in particular, are affected by the preconceived assumptions and biases of those who produce them. In this essay, I argue that the production of criminology is a cultural enterprise that reflects the attitudes and values of those who produce it. In my address for the Stockholm Prize, I summarize the main thesis of my Losing Legitimacy book and then discuss two recent projects that were influenced by the idea that strong social institutions reduce criminal behavior. The first examines the impact of the death of Freddie Gray in Baltimore in 2015 on crime and arrest rates. The second examines the impact of globalization on national homicide rates. In both cases, the results were unexpected. Policy Implications As scientists, it is critical that we evaluate research based on its theoretical soundness and methodological sophistication rather than whether it fits a currently hot topic or politically popular perspective. Science progresses by the constant process of evaluating theoretical propositions with empirical data—regardless of where those data lead us. Openness about crime and reactions to crime is no less important than honesty about the positive benefits of ice-cream consumption.